1988
DOI: 10.1016/0378-1097(88)90306-0
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of two 3-ketothiolases possessing differing substrate specificities in the polyhydroxyalkanoate synthesizing organism Alcaligenes eutrophus

Abstract: Two constitutive acetyl‐CoA acetyltransferases (3‐ketothiolases A and B) were purified from Alcaligenes eutrophus. Enzyme A was active with only acetoacetyl‐CoA and 3‐ketopentanoyl‐CoA, whereas enzyme B was active with all the 3‐ketoacyl‐CoAs (C4−C10) tested. Enzyme A appeared to be a tetramer (Mr 70 000) with identical subunits (Mr 44 000) and enzyme B had a similar Mr of 168 000 (containing Mr 46 000 subunits). Enzymes A and B had isoelectric points of 5.0 and 6.4, respectively. The stoichiometry of the reac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
59
0
4

Year Published

1990
1990
2009
2009

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(67 citation statements)
references
References 5 publications
4
59
0
4
Order By: Relevance
“…Haywood et al reported that 3 to 10% of the monomeric units of PHA accumulated from hexanoic acid are one or more C 2 units longer than the substrate used (10,13). It was suggested that the presence of these longer monomers is due to a condensation reaction of acyl-CoA molecules with acetyl-CoA catalyzed by the ␤-oxidation enzyme 3-ketothiolase (10). An additional copy of fadD in P. putida CA-3 could result in the production of higher concentrations of both fatty acyl-CoA esters and acetyl-CoA due to an increased flux through ␤ oxidation.…”
Section: Discussionmentioning
confidence: 99%
“…Haywood et al reported that 3 to 10% of the monomeric units of PHA accumulated from hexanoic acid are one or more C 2 units longer than the substrate used (10,13). It was suggested that the presence of these longer monomers is due to a condensation reaction of acyl-CoA molecules with acetyl-CoA catalyzed by the ␤-oxidation enzyme 3-ketothiolase (10). An additional copy of fadD in P. putida CA-3 could result in the production of higher concentrations of both fatty acyl-CoA esters and acetyl-CoA due to an increased flux through ␤ oxidation.…”
Section: Discussionmentioning
confidence: 99%
“…The phenotype of this mutant class was referred to as PHB-leaky. PHB-leaky mutants exhibited activities of all three PHBbiosynthetic enzymes; there was also no evidence that isoenzymes of the biosynthetic P-ketothiolase (25) or of the acetoacetyl coenzyme A reductase (26) were affected in these mutants. Measurements with reconstituted enzyme 5844 PRIES ET AL.…”
mentioning
confidence: 91%
“…In both Zoogloea ramigera (8,9,15,16,25,27,28) and Alcaligenes eutrophus (19,20), the condensation of two acetyl coenzyme A (CoA) units to form acetoacetyl-CoA by the enzyme 3-ketothiolase is followed by a stereospecific reduction step catalyzed by an NADP+-specific acetoacetyl-CoA reductase to form D-3-hydroxybutyryl-CoA, the substrate for PHB synthase. Both the 13-ketothiolase and acetoacetyl-CoA reductase are soluble cytosolic enzymes, whereas the PHB synthase is found attached to the PHB granules.…”
mentioning
confidence: 99%